Combined transcriptomic and proteomic analysis of the response to bile stress in a centenarian-originated probiotic Lactobacillus salivarius Ren. (November 2020) - Wang, Guohong; Zhai, Zhengyuan; Ren, Fazheng; Li, Zaigui; Zhang, Bing; Hao, Yanling
Graphical abstract: Highlights: The abundance of 129 genes and 34 proteins was significantly changed by bile. The barrier function of cells and the active extrusion of bile were enhanced. Enzymes responsible for protein refolding and antioxidant defense were induced. Bile-adapted cells expanded the utilization profile of carbon sources in gut. Abstract: Tolerance to bile stress is a crucial property for probiotics to survive in the gastrointestinal tract and exert their beneficial effects. In this work, transcriptomic analysis combined with two-dimensional electrophoresis revealed that the transcript levels of 129 genes and the abundance of 34 proteins were significantly changed in Lactobacillus salivarius Ren when exposed to 0.75 g/L ox-bile. Notably, carbohydrate metabolism shifted to the utilization of maltose and glycerol for energy production, suggesting that L. salivarius Ren expanded carbon sources profile for gut adaptation in response to bile. Moreover, the enzymes involved in cell surface charge modification and the cell envelope-located hemolysin-like protein were overproduced, which was supposed to hinder the penetration of bile. Then, the up-regulated ABC transporters could contribute to the extrusion of bile accumulated in the cytoplasm. Additionally, proteolytic system was activated to provide more amino acids for the synthesis and repair of proteins damaged by bile. Finally, γ-glutamylcysteine with antioxidant activity and oxidoreductases for redox homeostasis were increased to cope with the bile-induced oxidative stress. These findings provide new insights into the molecular mechanisms involved in bile stress response and adaptation in L. salivarius .